Artificial Intelligence Beyond Borders. - Boldea, Iulian (Caietele Echinox, 2025)
The present paper revolves around the concept of artificial intelligence and its impact on literature, culture and creative industries. Tools like ChatGPT, MidJourney and GitHub Copilot generate text, images and other media by modeling data patterns, improving efficiency in content creation, research and marketing. However, AI lacks emotional depth, moral discernment and individualized creativity. The aim of the paper is to situate AI within literary and philosophical frameworks, highlighting its algorithmic and fragmented nature, while emphasizing that human subjectivity, imagination and reflection remain irreplaceable. It calls for critical engagement with AI to balance technological benefits with the preservation of human creative expression.